PSIX-25 Documenting succession of the rumen microbial community in dairy calves. (30th November 2020) - Deblois, Courtney; Suen, Garret; Weigel, Kent; Hernandez, Laura; Steinberger, Andrew; Skarlupka, Joseph H; Sprecher, Dante; Eder, Morgan; Koller, Alexander; Gelsinger, Sandra
Abstract: Dairy cattle rely exclusively on the microbiota within their gastrointestinal tract for nutrient provisioning as they lack the endogenous enzymes needed to convert their plant-based diet into an accessible form. The acquisition of a fully functioning gut microbiome early in life is critical to survival of these animals. The establishment of a calf's gut microbiota has previously been characterized using proxies such as fecal sampling and destructive sampling methods, but it is unclear how accurate these methods are over time in the same animals. To address this, 10 dairy calves were cannulated at 3 weeks of age. Rumen liquid and rumen solid samples were collected biweekly in congruence with buccal swabs and fecal samples from 7–17 weeks of age and characterized using Illumina 16S rRNA V4 amplicon sequencing. Fecal and buccal samples contained similar amounts of shared operational taxonomic units (OTUs) to the rumen pre-weaning but separated post-weaning such that buccal samples contained nearly double the number of shared OTUs. Beta diversity showed that fecal communities more closely resemble the rumen than buccal but shift as the animals begin ruminating such that buccal communities more closely resemble the rumen. This suggests that fecal samples would serve as a more accurate proxy prior to weaning whereas buccal samples would more accurately represent the rumen after weaning. These data will be invaluable for researchers interested in understanding the acquisition, succession, and establishment of the calf rumen microbiota using non-invasive approaches.